2020
DOI: 10.3390/v12060687
|View full text |Cite
|
Sign up to set email alerts
|

Live Visualization of Hemagglutinin Dynamics during Infection by Using a Novel Reporter Influenza A Virus

Abstract: Live visualization of influenza A virus (IAV) structural proteins during viral infection in cells is highly sought objective to study different aspects of the viral replication cycle. To achieve this, we engineered an IAV to express a Tetra Cysteine tag (TC tag) from hemagglutinin (HA), which allows intracellular labeling of the engineered HA protein with biarsenic dyes and subsequent fluorescence detection. Using such constructs, we rescued a recombinant IAV with TC tag inserted in HA, in A/Puerto Rico/8/1934… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…Additionally, we demonstrated that the TMUV replicon was capable of expressing viral (glyco)proteins of AIV (HA), IBV (Spike), and IBDV (pVP2). HA was detected in the perinuclear region within electroporated cells, indicating that this viral glycoprotein was correctly routed to the cell surface as previously described for a reporter Influenza A virus (dos Anjos Borges et al, 2020). Indeed, HA was also detected at the cell surface.…”
Section: IIsupporting
confidence: 77%
“…Additionally, we demonstrated that the TMUV replicon was capable of expressing viral (glyco)proteins of AIV (HA), IBV (Spike), and IBDV (pVP2). HA was detected in the perinuclear region within electroporated cells, indicating that this viral glycoprotein was correctly routed to the cell surface as previously described for a reporter Influenza A virus (dos Anjos Borges et al, 2020). Indeed, HA was also detected at the cell surface.…”
Section: IIsupporting
confidence: 77%
“…HA was detected in the perinuclear region within electroporated cells, indicating that this viral glycoprotein was correctly routed to the cell surface as previously described for a reporter Influenza A virus. [ 35 ] Indeed, HA was also detected at the cell surface. For the TMUV replicon expressing pVP2, a cytosolic distribution was observed which is in agreement with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Research labs around the globe are devising newer and more robust techniques in order to identify novel ways to perform new antiviral screens. Using live confocal imaging, Anjos Borges et al [ 3 ] have used an innovative Hemagglutinin (HA)-Tetra Cysteine tag reporter IAV in an assay to screen chemical inhibitors of HA translocation.…”
mentioning
confidence: 99%